Mobile applications as a promotional tool of a tourist offer in protected areas - Mišković Ivana; Holodkov Vladimir; Radin Ivan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2015)
The rapid development of information and communications technology (ICT) in recent decades has resulted not only in drastic increase in speed of the information flow, but also in the number of users of mobile devices. This trend has been recognized and used by many industries, including tourism. The use of specialized application software, compatible with the modern 'smartphones', the interaction between tourists and tourist destinations received a whole new dimension. This article aims at analyzing the ways in which the two seemingly incompatible concepts - tourism in protected nature and advanced communication technologies - can complement each other in order to create, improve and promote ecotourism products. Furthermore, it will analyze the latest trends in the development of mobile applications used in tourism industry and present examples of good practice in protected areas in Serbia and abroad. Due to the fact that mobile applications and technological innovations are relatively new and so far very few researchers have involved in the research of their effects on the users' satisfaction and their behavior, this paper will give guidelines for future research on this topic.